Change of Cerebral Blood Flow After a Successful Pharmacological Treatment of Phantom Bite Syndrome: A Case Report. Issue 2 (March 2019) - Umezaki, Yojiro; Tu, Trang T. H.; Toriihara, Akira; Sato, Yusuke; Naito, Toru; Toyofuku, Akira
Abstract : Background: "Phantom bite syndrome, " a persistent complaint of an uncomfortable bite sensation with no obvious occlusal abnormal finding, recently was suggested to be related with central nervous system dysfunction. Here, we report a case of phantom bite syndrome in which the occlusal discomfort was improved with mirtazapine and aripiprazole combination parallel with regional cerebral blood flow change. Case report: A 60-year-old-female patient came to our clinic with the chief complaint of a "loosely bite" after dental treatment and various uncomfortable sensations of body sites. One year after the medication therapy, the prosthodontic retreatment was carried out successfully, and a good outcome was obtained for over 24 months so far. In addition, a subsequent change of regional cerebral blood flow was observed in single-photon emission computed tomography: the right and left asymmetry of cerebral blood flow in the frontal lobe has disappeared along with the improvement to the symptoms improvement. Conclusions: This case suggests that some central nervous system dysfunction involving dopaminergic system might be related to the pathophysiology of phantom bite syndrome.